2018
DOI: 10.3389/fnhum.2018.00200
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Communication in Aphasia: Perception and Production of Co-speech Gestures During Face-to-Face Conversation

Abstract: The role of nonverbal communication in patients with post-stroke language impairment (aphasia) is not yet fully understood. This study investigated how aphasic patients perceive and produce co-speech gestures during face-to-face interaction, and whether distinct brain lesions would predict the frequency of spontaneous co-speech gesturing. For this purpose, we recorded samples of conversations in patients with aphasia and healthy participants. Gesture perception was assessed by means of a head-mounted eye-track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…PWA Mb1 produced 578 words and 119 communicative gestures, Mw2 produced 580 words and 68 communicative gestures, Mb2 used 750 words and 53 communicative gestures, Mw1 used 733 words and 19 communicative gestures and Wtm produced 818 words and 22 communicative gestures. My results are also concordant with those of Preisig (2018), who found that persons with more severe aphasia (but not with apraxia) produce more meaningful gestures than mildly affected people.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…PWA Mb1 produced 578 words and 119 communicative gestures, Mw2 produced 580 words and 68 communicative gestures, Mb2 used 750 words and 53 communicative gestures, Mw1 used 733 words and 19 communicative gestures and Wtm produced 818 words and 22 communicative gestures. My results are also concordant with those of Preisig (2018), who found that persons with more severe aphasia (but not with apraxia) produce more meaningful gestures than mildly affected people.…”
Section: Discussionsupporting
confidence: 87%
“…This fact confirms that gestures can transmit important parts of information, but are also largely dependent on speech. Preisig et al (2018) explored Swiss PWA and the main question of their study (2018, p. 9) concerned the question of how PWA perceive and produce co-speech gestures during face-to-face interaction. They examined the impact of co-speech gestures at the level of perception by the eye-tracking method (using voxel-based lesion-symptom mapping, VLSM) in order to connect the production of co-speech gestures and the localization of brain injury.…”
Section: Recent Research On Gestures In Pwamentioning
confidence: 99%
“…Aphasia is an acquired disorder that can affect both language production and comprehension ( Preisig et al, 2018 ). While language and gesture production have been vastly studied, literature on gesture comprehension is quite sparse.…”
Section: Investigating the Relationship Between Iconic Gestures And Languagementioning
confidence: 99%
“…More recently, several studies investigated co-speech gesture-speech integration in aphasia ( Eggenberger et al, 2016 ; Cocks et al, 2018 ; Preisig et al, 2018 ). Preisig et al (2018) showed that during live conversations, co-speech gestures (of all types) attracted the attention of aphasic patients and were more fixated than abstract gestures. The authors suggested that these patients may benefit from the bimodal information presentation to compensate a verbal deficit ( Preisig et al, 2018 ).…”
Section: Investigating the Relationship Between Iconic Gestures And Languagementioning
confidence: 99%
See 1 more Smart Citation